A tale of scale: Plot but not neighbourhood tree diversity increases leaf litter ant diversity. Issue 2 (19th October 2019) - Skarbek, Carl J.; Noack, Merle; Bruelheide, Helge; Härdtle, Werner; von Oheimb, Goddert; Scholten, Thomas; Seitz, Steffen; Staab, Michael
Abstract: Diversity of producers (e.g. plants) usually increases the diversity of associated organisms, but the scale (i.e. the spatial area of plant diversity considered) at which plant diversity acts on other taxa has rarely been studied. Most evidence for cross‐taxon diversity relations come from above‐ground consumers that directly interact with plants. Experimental tests of plant diversity effects on elusive organisms inhabiting the leaf litter layer, which are important for nutrient cycling and decomposition, are rare. Using a large tree diversity experiment, we tested whether tree diversity at the larger plot (i.e. community) or the smaller neighbourhood scale relates to the abundance, species richness, functional and phylogenetic diversity of leaf litter ants, which are dominant organisms in brown food webs. Contrary to our expectations of scale‐independent positive tree diversity effects, ant diversity increased only with plot but not neighbourhood tree diversity. While the exact causal mechanisms are unclear, nest relocation or small‐scale competition among ants may explain the stronger tree diversity effects at the plot scale. Our results indicate that even for small and less mobile organisms in the leaf litter, effects of tree diversity are stronger at relatively larger scales. The finding emphasizes the importance of diverse forest stands, in which mixing of tree species is not restricted to small patches, for supporting arthropod diversity in the leaf litter. Abstract : The authors show that tree diversity at the plot (i.e. community) but not at the neighbourhood scale increases leaf litter ant diversity. This indicates that cross‐taxon diversity congruence may be more pronounced at larger scales.